In a Δ ABC, with usual notations prove that: (a -bcos C) /(b -a cos C )= cos B/ cos A - Mathematics and Statistics
In a Δ ABC, with usual notations prove that:` (a -bcos C) /(b -a cos C )= cos B/ cos A`
Consider L.H.S. `=(a-bcosC)/(b-acosC)`
`=(b cosC+c cosB-b cosC)/(a cosC+c cosA-a cosC)`
`=(c cosB)/(c cosA) `
Concept: Solutions of Triangle
Is there an error in this question or solution?
why create a profile on Shaalaa.com?
1. Inform you about time table of exam.
2. Inform you about new question papers.
3. New video tutorials information.